2020
DOI: 10.1097/md.0000000000018687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nighttime and weekends on outcomes of emergency trauma patients

Abstract: The impact of time of day or day of week on the survival of emergency trauma patients is still controversial. The purpose of this study was to evaluate the outcomes of these patients according to time of day or day of week of emergency admission by using data from the nationwide Japan Trauma Data Bank (JTDB). This study enrolled 236,698 patients registered in the JTDB database from 2004 to 2015, and defined daytime as 09:00 am to 16:59 pm and nighttime as 17:00 pm to 08:59 am, weekdays as Monday to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…Concerning neurosurgical procedures, Desai et al reported an increased morbidity and mortality rate among pediatric neurosurgical emergencies admitted during out-of-office hours [10]. Hirose et al found that in-hospital mortality of emergency trauma patients was significantly higher during nighttime, however, there was no difference regarding weekdays and weekends [19]. In contrast, Rumalla et al found no association between weekend admission and mortality among traumatic subdural hematoma patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning neurosurgical procedures, Desai et al reported an increased morbidity and mortality rate among pediatric neurosurgical emergencies admitted during out-of-office hours [10]. Hirose et al found that in-hospital mortality of emergency trauma patients was significantly higher during nighttime, however, there was no difference regarding weekdays and weekends [19]. In contrast, Rumalla et al found no association between weekend admission and mortality among traumatic subdural hematoma patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…The “weekend effect” refers to the phenomenon in which patients admitted during weekends may have more fatal outcomes than those admitted during the weekdays 7 , 8 . Poor performances in hospitals are considered a reason for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Research staff listed the following possible factors for this conclusion: age-related effect of sleep loss, difference in responsibilities between staff and fellows in the daytime, and supervision of nighttime fellows. Moreover, a nationwide study based on the Japan Trauma Data Bank [ 45 ] from 2004 to 2015 divided the day into 2 shifts (daytime, 9 am to 4:59 pm , and nighttime, 5 pm to 8:59 am ) and found a significant daytime decrease in deaths among emergency trauma patients, both in the emergency room and at hospital discharge; there was no association between weekday/weekend and outcomes. In addition, a systematic review [ 46 ] of 40 observational studies that included about 3 million patients concluded that postoperative risk of mortality is associated more with surgery performed at night/after-hours than surgery performed during the day.…”
Section: Discussionmentioning
confidence: 99%